2021
DOI: 10.1051/matecconf/202133201014
|View full text |Cite
|
Sign up to set email alerts
|

Selected aspects of diagnosing material removal machining processes state

Abstract: The article presents the results of works on the analysis of the possibility of using force measurements to determine the state of the machining process, both in relation to the phenomena occurring during machining and the workpiece itself compared to acoustic emission signal (AE). The research and analyzes were carried out for the commonly used material removal processes of objects; turning, milling, grinding and drilling. Various materials were processed - metal alloy Hardox 400 as well as fiber composite ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…cutting forces and torque, which were diagnostic signals of the state of the process. As in the previous study [13], the determined changes in the value of cutting forces were a good diagnostic signal of the process status. During the experiment, it was found that a large amount of heat was generated (measurements of temperature changes were not the subject of the study), which was manifested by the formation of smoke in the place where the hole was made and glowing of the machined surface.…”
Section: Results Measurementssupporting
confidence: 73%
See 1 more Smart Citation
“…cutting forces and torque, which were diagnostic signals of the state of the process. As in the previous study [13], the determined changes in the value of cutting forces were a good diagnostic signal of the process status. During the experiment, it was found that a large amount of heat was generated (measurements of temperature changes were not the subject of the study), which was manifested by the formation of smoke in the place where the hole was made and glowing of the machined surface.…”
Section: Results Measurementssupporting
confidence: 73%
“…in the field of determining trust forcee and torque [1,2,20], modeling temperature or forces occurring in the process [3,7,9,11,15,18] as well as testing the material itself, in particular its abrasive properties or abrasion resistance [10]. Based on the review of the literature in the field of the study, it was found possible to diagnose and monitor the state of the removal process of fiber-reinforced polymer composites on the basis of forces and acoustic emission (AE) [4,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…cutting forces and torque, which were diagnostic signals of the state of the process. It was shown, similarly to previous works [15,16], that measurements of changes in the values of forces or torque can be a good diagnostic signal of the state of the cutting process. The experiment was stopped when increased force values were obtained in order to avoid catastrophic wear of the tool.…”
Section: Discussionsupporting
confidence: 75%
“…1 shows force Fx, Fy, Fz and Fig. 2 -torque Mz values changes during whole milling process [15,16]. The values of the total cutting force were determined from the relationship:…”
Section: Measurements Resultsmentioning
confidence: 99%
See 1 more Smart Citation